2017
DOI: 10.3390/ma10091040
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Silane Coupling Agent on Tribological Properties of Hemp Fiber-Reinforced Plant-Derived Polyamide 1010 Biomass Composites

Abstract: Abstract:We have studied the effects of silane coupling agents used for the surface treatment of fiber on the tribological properties of hemp fiber (HF) reinforced plant-derived polyamide 1010 (PA1010) biomass composites. Hemp fibers were surface-treated by two surface treatment methods: (a) alkali treatment by sodium hydroxide solution and (b) surface treatment by silane coupling agents. Three types of silane coupling agents, namely aminosilane, epoxysilane and ureidosilane were used. These HF/PA1010 biomass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 48 publications
1
45
0
Order By: Relevance
“…These results are in total agreement with those reported by Zhu et al with flax-fibre-based composites, a different polymer matrix and different surface treatments, i.e., mercerization, silanization, acylation and peroxide treatments to increase particle-polymer interaction [ 46 ]. Nishitani et al also reported the positive effect of silane coupling agents in polyamide 1010/hemp fibre composites showing an improved tribological response due to increased polymer-reinforcement interaction [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…These results are in total agreement with those reported by Zhu et al with flax-fibre-based composites, a different polymer matrix and different surface treatments, i.e., mercerization, silanization, acylation and peroxide treatments to increase particle-polymer interaction [ 46 ]. Nishitani et al also reported the positive effect of silane coupling agents in polyamide 1010/hemp fibre composites showing an improved tribological response due to increased polymer-reinforcement interaction [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…It had been proved that chemical treatments of natural fiber surface were an effective way to improve the interfacial compatibility and adhesion of natural fiber-reinforced polymer composites [ 8 ]. Several types of chemical treatment methods were developed for surface modification of natural fiber, including silane treatment [ 9 , 10 ], acetylation treatment [ 11 ], benzoylation treatment [ 12 ], acrylation and acrylonitrile grafting [ 13 , 14 ], dopamine treatment [ 15 ], N-methylol acrylamide grafting [ 4 ], and so on. Alkali treatment with sodium hydroxide is one of the most widely used chemical treatment methods for natural fibers [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…5 wt% fiber content proved to be superior considering its lower wear rate and highest friction stability at 0.93. Nishitani et al [92] studied the influence of alkali and silane surface treatment on friction and wear characteristics of hemp fiber composites in plant-based polyamide biomass polymer matrix. Fibers, after treated with 5% NaOH and 1% silane coupling agents, were cured in the air for 24 hours and in oven at 80 C for 5 hours.…”
Section: Tribological Behaviormentioning
confidence: 99%